Living Abroad, Facing Risks: How Prepared Are Indonesian Diaspora Students for Disasters? - Nugroho, Agung; Untarti, Reni; Irawan, Dedy; Mareza, Lia; Pria Wibowo, Anggun (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study aims to analyze the level of preparedness among Indonesian diaspora students in the face of potential disasters, particularly earthquakes and tsunamis, and to identify aspects of preparedness that still need to be improved. Method: This study employed a quantitative approach using a survey method involving 30 fifth-grade students at Sekolah Indonesia Kuala Lumpur (SIKL), Malaysia. The instrument used was the LIPI-UNESCO/ISDR Disaster Preparedness Questionnaire Series 3, which covers four main parameters: knowledge and attitudes, emergency response plans, early warning systems, and resource mobilization. The data was analyzed by calculating the readiness index for each parameter and the overall student readiness index. Results: The research findings indicate that the disaster preparedness level of diaspora students falls into the